2007
DOI: 10.1248/bpb.30.2365
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Drug Release of DE-310, Macromolecular Prodrug of DX-8951f, and Cathepsins Activity in Several Tumors

Abstract: Utilization of drug delivery systems is an attractive approach to improving efficacy and safety of anticancer drugs. Long-circulating macromolecular or particulate carriers are known to preferentially accumulate in solid tumors, due to the "enhanced permeability and retention (EPR)" effect, 1) i.e., leakiness of tumor angiogenic blood vessels and lack of effective lymphatic drainage. SMANCS (neocartinostatin polymer conjugate), Doxil (doxorubicin liposome), and Daunozome (daunorubicin liposome) 2,3) that explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…We showed that inhibition of Cathepsin B significantly decreased the proliferation of cancer cells, and that suppression of Cathepsin B significantly attenuated migration and invasive activity of HEC-1A cells. These findings are in agreement with those reported for other types of tumors (26,27). Taken together, these results suggest Cathepsin B has metastatic potential in EC cells.…”
Section: Discussionsupporting
confidence: 93%
“…We showed that inhibition of Cathepsin B significantly decreased the proliferation of cancer cells, and that suppression of Cathepsin B significantly attenuated migration and invasive activity of HEC-1A cells. These findings are in agreement with those reported for other types of tumors (26,27). Taken together, these results suggest Cathepsin B has metastatic potential in EC cells.…”
Section: Discussionsupporting
confidence: 93%
“…295 The release of drug through the amino acid linker cleavage was also determined to be mainly due to the activity of cathepsin B in the tumor. 296 Another study shows evidence of meningocele induction in rat fetuses after their mothers received four i.v. doses of 0.3 mg/kg or a single dose of 1 mg/kg.…”
Section: Macromolecular Architectures For Passive Drug Deliverymentioning
confidence: 99%
“…In this context, we combinatorially synthesized 225 fluorogenic macromolecular prodrugs with a CM-Dex-PA backbone and evaluated sequence dependence of amino acid spacers on the rate of drug release by tumor-associated proteases. We intended to evaluate structure-activity relationship of drug release under rather physiologically relevant conditions (i.e., tumor cell homogenates) than by individual cathepsins, since it was obvious that multiple proteases including cathepsins B and L are responsible for hydrolysis of the same type of macromolecular prodrugs (17).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the pH dependence on the cathepsin activities associated with Meth A tumor homogenate (17), the drug release assay of the conjugates was performed at pH 4.5. When CM-Dex-PA-Gly-Gly-P 2 -P 1 -DNS was incubated, not only DNS but its peptide conjugate (P 1 -DNS and P 2 -P 1 -DNS) were detected by HPLC.…”
Section: Drug Release Assay Of Dns Conjugates By Meth a Homogenatementioning
confidence: 99%